Comparative structural, colloidal, and kinetic evaluation of yeast, soy, and whey proteins: uncovering the modification needs of yeast protein - Siliang Wu; Kewei Chen; Wen Li; Xueying Song; Yihan Mu; Mouming Zhao; Guowan Su (Food Hydrocolloids, 2026)

Enhancing bioaccessibility and interfacial functional properties of yeast protein via the strategy of two-stage ultrasound processing: insights from the Bayesian optimization, structural characterization and kinetics - Siliang Wu; Yuting Liu; Wen Li; Kewei Chen; Yihan Mu; Mouming Zhao; Guowan Su (Food Hydrocolloids, 2026)

Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Unlocking the antioxidant potential of wheat gluten: structural transitions and peptide release driven by ultrasonication-assisted pH shifting - Peng Cheng; Xueying Song; Yihan Mu; Siliang Wu; Mouming Zhao; Guowan Su (Food Chemistry, 2026)

Efficient fractionation of reed biomass by inorganic salt-driven seawater/ethanolamine pretreatment for fermentable sugars and N-containing lignin - Hao Tong; Meizhen Jiao; Bo Mu; Bin Li; Shihao Su; Yehan Tao; Jinwen Hu; Jian Du; Jie Lu; Chenglong Fu; Haisong Wang (Chemical Engineering Journal, 2026)

Sulfuric acid-induced microphase separation strengthens poly(acrylic acid) hydrogels - Zheng Luo; Yuan Feng; Meng Mu; Xing Zhang; Heng Liu; Mingmin Zhang; Xin Su; Yujun Feng (Chemical Engineering Journal, 2026)

Land-use change dominates amphibian biodiversity loss, with antagonistic interactions with climate change in the karst region of Guizhou, China - Jing Liu; Shize Li; Gang Wei; Tuo Shen; Lang Mu; Haijun Su (Journal of Environmental Management, 2026)

Limited enzymatic hydrolysis reshapes whey protein antigenicity, taste profile, and techno-functional properties - Meng-Qi Liu; Wen-Qi Liang; Di Su; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2026)

Protein glutaminase–mediated deamidation improves the hydration properties of spray-dried micellar casein powders by coupling hierarchical porosity with surface charge and hydrophobicity modulation - Yi-Fang Gao; Stella Zhu; Di Su; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2026)

Sustained and controlled release of natural volatile organic compounds from hydrophilic–lipophilic balance-optimized phytoncide emulsion–zeolite composites for indoor application - Soo-Min Jeong; Yu-Jeong Ko; Mu-Seong Lee; Young-Kyu Lee; Su-Gwang Jeong (Journal of Hazardous Materials, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

The role of polysaccharide ionic character in modulating lubrication behavior of WPI-based composite hydrocolloids - Pingping Tan; Yuanbo Zhong; Zhen Zhang; Wanying Su; Longyang Liang; Jianshe Chen; Ruojun Mu (Food Chemistry, 2026)

Precision design of hydrogel polymer nanoparticles: How side-chain spatial arrangement and length matching govern antibacterial activity, physiological robustness, and selectivity - Weixiang Zhang; Weicheng Tang; Bo Li; Shiqi Lin; Mu Yuan; Lei Su; Wenfeng Tan; Gailing Yuan; Mingming Liu (Chemical Engineering Journal, 2026)

Orbital symmetry matching-mediated synergistic N2/CO2 activation on Cu-Co3O4 for photocatalytic urea synthesis - Meng Qiao; Yan-Fei Mu; Ji-Li Zhou; Su-Xian Yuan; Meng-Ran Zhang; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2026)

Age- and sex- related patterns in hematobiochemical and anthropometric parameters of Macaca monkeys - Hyeon-Mu Cho; Se-Hee Choe; Hye-Ri Park; Ja-Rang Lee; Min-Gyeong Ko; Yun-Jung Lee; Kang Jin Jeong; Bon Sang Koo; Kyung Seob Lim; Gyu-Seo Bae; Eun Su Jeon; Philyong Kang; et al. (GeroScience, 2026)

Characterization and mechanistic insights into changes in flavor compounds of yeast extract during the evaporative process - Yuting Liu; Siliang Wu; Xueying Song; Yihan Mu; Mouming Zhao; Guowan Su (Innovative Food Science & Emerging Technologies, 2026)

Decoding novel umami peptides from soy protein isolate hydrolysate: Mechanistic insights via multisensory techniques, machine learning and molecular docking - Xueying Song; Dipeng Mei; Yihan Mu; Peng Cheng; Siliang Wu; Chenchen Cao; Guowan Su (Food Bioscience, 2026)

Predictive Multi-Physics coupling coal combustion model under rapid heating - Hanjian Li; Ying Zhao; Shichen Ding; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Huanying Chi (Fuel, 2026)

Multi-omics insights into microbial communities and key flavor formation mechanisms of sweet flour paste under sunroom fermentation mode - Yuanyuan Chen; Qi Qi; Danyu Yan; Xintong Hu; Chi Zhang; Yingchun Mu; Wei Su; Yu Mu (Food Bioscience, 2026)

Comparative assembly mechanisms of microbial communities shape flavor metabolism in high-and low-salt soy sauce fermentation - Danyu Yan; Qi Qi; Xinru Ma; Yanfeng Fu; Linpei Liu; Yingchun Mu; Wei Su; Yu Mu (Food Bioscience, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Corrigendum to ‘ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection’ [Pesticide Biochemistry and Physiology 220 (2026) 107056] - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

Comparative and experimental analyses of meiofaunal community responses to submerged marine debris in Ulleung Island, Korea - Mu Gyeom Jeon; A-Young Shin; Won Gi Min; Je-Hyeok Oh; Min-Su Woo; Ok Hwan Yu; Chulwoong Oh; Dongsung Kim (Marine Pollution Bulletin, 2026)

Species-specific eDNA monitoring and multivariate analysis for early warning of marine harmful organisms in a semi-enclosed Coastal Bay - Hwa-Seong Son; Kun-Woo Yun; Min-Jun Seong; Su Min Kim; Seung-Min Lee; Mu-Chan Kim (Regional Studies in Marine Science, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Study on the mechanism of mixed biochar enhancing methane production in anaerobic digestion of corn straw - Huilin Zhang; Siyu Zhang; Pujie Wei; Xinyue Zhao; Hong Chang; Zeyan Mu; Xu Zhang; Wei Liu; Xudan Liu; Xiaohong Su; Xin Wang (Biocatalysis and Agricultural Biotechnology, 2026)

Effect of CO2 and H2O on pyrolysis characteristics and structural evolution of Zhundong coal under rapid heating rate - Huanying Chi; Shichen Ding; Ying Zhao; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Hanjian Li (Fuel, 2026)

A robust system for somatic embryogenesis and shoot organogenesis in Begonia grandis subsp. sinensis (A. DC.) Irmsch and genetic fidelity assessment of the regenerants - Feimin Ma; Zhengli Shan; Haonan Su; Ruijing Han; Wenjing Zhou; Mu Ze; Ming Dong; Qinggui Wu; Lijuan Zou (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Long Non-Coding RNA PVT1 Inhibits Apoptosis Through the miR-30d-5p/CaMKIIδ Axis in Hypoxic–Ischemic Brain Injury - Fengyan Zhao; Junyan Liu; Zihong Xiong; Lingyi Huang; Yuanyuan Zhao; Shiping Li; Junjie Ying; Qian Liu; Shaopu Wang; Xiaojuan Su; Jun Tang; Yi Qu; et al. (Molecular Neurobiology, 2026)

Acute effects of two different combined exercise modalities on executive function and circulating neurotrophic factors in young healthy adults - Yi-Hung Liao; Toby Mündel; Ying-Chu Chen; Shiow-Chwen Tsai; Kuo-Cheng Wu; Mu-Tsung Chen; Li-Chen Lee; Chih-Peng Su; Yu-Kai Chang; Chung-Yu Chen (European Journal of Applied Physiology, 2026)

Excavation instability with end restraint effect under high stress: insights from True-Triaxial simulation experiments - Ting Zhang; Si-Qiao Wang; Shi-Hong Wu; Mu-Qing Su; Jian-Zhi Zhang; Yong Niu (Bulletin of Engineering Geology and the Environment, 2026)

Ground validation of dust multi-properties analyzer onboard Tianwen-2 - Xu Tan; Cunhui Li; Jiajie Wang; Zhongcheng Mu; Zecheng Cui; Meng Chen; Xin Ren; Xiaodong Liu; Yan Su; Wei Wang; Renhao Tian; Jiawei Li (Advances in Space Research, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Prediction and analysis of polyvinylidene fluoride membrane pyrolysis reaction based on machine learning framework - Hong Su; Yadong Ge; Xiaohua Wang; Lan Mu; Beibei Yan; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Iron-doped biocarriers enhanced nitrogen removal from saline wastewater in an unplanted constructed wetland-microbial electrolytic cell system - Longqiang Yi; Changyuan Liu; Xinyu Rong; Kexin Li; Ruina Zhang; Xin Su; Xinting Mu; Li Wan; Yinghai Wu; Rui Han (Journal of Environmental Management, 2025)

Comparison of compositional, structural, and functional characteristics in walnut (Juglans regia L.) proteins prepared from walnut meal: Effects of extraction and isolation methods - Yihan Mu; Xueying Song; Siliang Wu; Dongxiao Sun-Waterhouse; Geoffrey I.N. Waterhouse; Mouming Zhao; Guowan Su (Food Chemistry, 2025)

Golgi-associated TRAF6 as a regulator of protein convertase FURIN for insulin receptor precursor processing - Minjun Liu; Kun Zhou; Yang Sheng; Wen Zhang; Qiaoli Chen; Ziyue Chen; Xinyu Yang; Yuxin Jin; Fangtong Liu; Yinqiu Mu; Shu Su; Weikuan Feng; et al. (Science China Life Sciences, 2025)

The interaction between COX-2 and endoplasmic reticulum stress is involved in liver ischemia–reperfusion injury in mice - Chen Liang; Liping Guo; Xinyan Tian; Zhidan Mu; Mingyang Chen; Yarong Hu; Juan Su (Molecular Biology Reports, 2025)

Predicting internal carotid artery system risk based on common carotid artery by machine learning - Yuhao Tong; Qingyi Zhang; Feng Zhang; Weidong Mu; Steven W. Su; Lin Liu (Medical & Biological Engineering & Computing, 2025)

BmeIF4E2 promotes AcMNPV infection in the silkworm, Bombyx mori, by direct interaction - Xin-Yi Ding; Jiang-Zhi Su; Wen-Jing Yu; Qian-Qian Jiao; Zuo-Min Shao; Ai-Jun Wan; Sheng Qin; Xia Sun; Xue-Yang Wang; Ding-Ding Lü; Mu-Wang Li (Pesticide Biochemistry and Physiology, 2025)

Metagenomics and binning analysis unveiled the diversity and transfer patterns of antibiotic resistance genes in traditional pickled vegetables - Hui Wang; Xindi Mu; Tingting Su; Xiyuan Yang; Lei Xu; Di Yao; Liangyu Li (Food Bioscience, 2025)

Effects of β-hydroxy-β-methylbutyrate inclusion on growth performance and fillet quality of olive flounder Paralichthys olivaceus fed low fishmeal based diets - Chaoqing Wei; Zhenxia Su; Cancan Xia; Lu Li; Zhicheng Song; Hua Mu; Hanliang Cheng; Jianhe Xu; Zhiguo Dong; Binlun Yan; Lu Zhang (Aquaculture, 2025)

2.2-billion-year-old KREEP-rich volcanism on the Moon - Mu-Han Yang; Qian W.L. Zhang; Qiu-Li Li; Ross N. Mitchell; Richard W. Carlson; Zhu-Yin Chu; Yu Liu; Yi Chen; Shun Guo; Ding-Shuai Xue; Bin Su; Xu Tang; et al. (Science Bulletin, 2025)

Experimental research on drift of rescue targets in a basin under controllable wind-wave-current environment - Jiaqian Wang; Hao Qin; Haiwen Tu; Daosheng Wang; Zhengzhou Li; Bo Li; Hanxiang Su; Chuanfeng Liu; Lei Qin; Lin Mu (Ocean Engineering, 2025)

Optimizing biogas residue composting: Impact of biochar and zeolite co-loaded with lignocellulose-degrading microbial agents on degradation, humification, and microbial ecology - Hong Chang; Ruian Lin; Xiaohong Su; Xinrui Xu; Wei Liu; Yilin Zhang; Zeyan Mu; Xin Wang; Anina James; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

Integrated machine learning model for prediction of nutrients contents and maturity in rural organic solid wastes aerobic composting - Hao Peng; Lan Mu; Yingjin Song; Hong Su; Yadong Ge; Zhanjun Cheng; Rundong Li; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Releasing ACE-inhibitory peptides from walnut protein via pulsed electric field: A multiscale mechanism-structure-function investigation - Xueying Song; Siliang Wu; Chenchen Cao; Yihan Mu; Ying Li; Ruili Liu; Guowan Su (Innovative Food Science & Emerging Technologies, 2025)

Soybean protein isolate hydrolysate addition during fermentation of soybean meal with Aspergillus oryzae enhances the release of umami components in subsequent hydrolysis process - Yihan Mu; Hui Kang; Xueying Song; Chenchen Cao; Dongxiao Sun-Waterhouse; Geoffrey I.N. Waterhouse; Mouming Zhao; Guowan Su (Food Bioscience, 2025)

Multi-omics investigation into microbial community succession and flavor compound dynamics during post-fermentation of Doubanjiang - Ling Chen; Wei Su; Yingchun Mu; Zhuo Chen; Yu Jiao; Linzhu L; Huayan Luo; Zhongle Lu (Food Bioscience, 2025)

Comparative analysis of rural organic waste treatment: greenhouse gas emissions, economics, and energy flow - Hao Peng; Lan Mu; Yingjin Song; Dan Zeng; Hong Su; Zhanjun Cheng; Rundong Li; Guanyi Chen (Biomass and Bioenergy, 2025)

Behaviors of suction bucket foundations in sands under vertical tensile load and seismic action - Xinglei Cheng; Yuming Su; Kun Mu; Dechun Lu; Jianxin Zhang; Liqiang Sun (Soil Dynamics and Earthquake Engineering, 2025)

Nitrogen uptake and nitrification in the Changjiang estuary - Xing Hou; Chongcong Liu; Guodong Song; Jinglong Mu; Wen Liang; Haoming Xu; Nian Wu; Wenqi Xu; Su Mei Liu (Marine Environmental Research, 2025)

Biogeography and Niche Evolution of Odorrana schmackeri Complex in Southern China - Shize Li; Bin Wang; Jing Liu; Haijun Su; Gang Wei; Lang Mu; Tuo Shen; Zhitong Lyu; Yingyong Wang; Houqiang Xu (Journal of Biogeography, 2025)
Aim The Odorrana schmackeri complex (OSC), widely distributed across southern China, presents intriguing mysteries regarding its diversification dynamics. Resolving these evolutionary enigmas would establish a crucial foundation for understanding biogeographic evolution in this topographically complex region. Therefore, we integrated phylogenetic, demographic, and ecological niche analyses to elucidate the roles of ancient tectonism, Quaternary climatic fluctuations, and niche evolution in shaping its diversification and distribution. Location Southern China. Methods Using two mitochondrial and eight nuclear genes, we reconstructed phylogenetic relationships, estimated divergence times and assessed population dynamics. Ecological niche models (ENMs) were optimised via the ‘Kuenm’ package, and niche overlap, equivalency, and similarity were quantified using the ‘ecospat’ R package. Acestral niche and climatic tolerances reconstruction were used in the ‘phyloclim’ package. Results The OSC comprises nine species and originated from a mid‐Miocene ancestor (~12.55 Ma). Mitochondrial phylogeny resolved four deeply divergent clades, while nuclear gene phylogeny revealed incomplete lineage sorting (ILS) and historical gene flow (STRUCTURE, K = 7; JML, p > 0.05). Post‐last glacial maximum (LGM) expansions (~0.02 Ma) facilitated secondary contact in sympatric zones, where niche conservatism dominated between sister species. Ancestral niche reconstruction identified precipitation variables as key drivers of early divergence, while thermal tolerances evolved conservatively. The results indicated that Miocene uplift of the Qinghai‐Tibet Plateau (~12.55–8.70 Ma) promoted southward expansion, while Pliocene‐Pleistocene (~5.58–2.40 Ma) river reorganisations fragmented and later connected populations. Main Conclusions The OSC's diversification reflects the interplay between Miocene–Pliocene tectonism and Quaternary climatic cycles. While ancestral niche divergence along precipitation gradients initiated speciation, post‐LGM sympatry favoured conservatism in thermal microhabitats. Combining multilocus phylogenetics, demographic inference, and niche modelling resolves the rapid‐radiating models in the frog complex and highlights the dynamic roles of landscape features in shaping biogeographic patterns of them.

Identifying the Alkaline Tolerance-Related Genes Through Transcriptome Analysis of Halomonas alkalicola CICC 11012 s - Lei Zhai; Shuaicheng Mu; Ruina Liu; Rui Liu; Geer Lin; Qi Han; Su Yao (Current Microbiology, 2025)

MoS2-intercalated montmorillonite nanostructure coupled with N-doped carbon-encapsulated CoMn bimetallic nanocage: A stability-enhancing strategy for peroxymonosulfate activation to pollutant degradation - Xudong Liu; Zhinan Xie; Min Li; Jiarong Mu; Weihong Wang; Chunfang Du; Yiguo Su (Journal of Environmental Chemical Engineering, 2025)

Metatranscriptomics reveals the effect of fermentation by Pediococcus acidilactici and Rhizopus oryzae on the quality of mutton sausages and the mechanism of odor metabolism - Nuo Chen; Weiyi Fu; Li Jiang; Nian Zhang; Yingchun Mu; Wei Su (Food Chemistry, 2025)

Specific glycomacropeptide detection via polyacrylamide gel electrophoresis with dual imaging and signal-fusion deep learning - Yiren Cao; Youli Tian; Ke-Er Chen; Yixin Ma; Qiang Zhang; Weiwen Liu; Zhishen Mu; Shengpeng Su; Chengxi Cao (Food Chemistry, 2025)

Microbial absolute quantification and metabolomics reveal the impact of partial KCl substitution for NaCl on the flavor quality of Zao Chili - Kangli Yang; Wei Su; Yingchun Mu; Xiaomin Liu; Yuxia Liu; Yongxin Lu (Food Bioscience, 2025)

Predicting and regulating potential zone for heavy metal re-contaminated farmland: Case study in Taiwan - Jieh-Haur Chen; Mu-Chun Su; Meng-Fen Yeh; Wei-Jen Lin; Tzuyang Yu; Ming-Chung Yeh (Environmental Development, 2025)

Association Between Mixed Metal Exposures and Female Infertility: A Large Cross-sectional Study - Yunan He; Xiaoxiao Su; Zhiping Niu; Bolun Zhang; Hui Mu; Lu Wang; Yuanqing Yao; Xiaohong Wang (International Journal of Environmental Research, 2025)

How the Labor Mobility Impact Farmers’ Sustainable Livelihoods in Mountainous Regions: Evidence from Qinling-Daba Mountains, China - Huizhen Su; Xueyan Zhao; Fangfang Mu; Hainan Yang (Chinese Geographical Science, 2025)

Role of myostatin promoter mutations in growth and molting regulation of Macrobrachium rosenbergii - Qiyao Su; Jie Wei; Yakun Wang; Bai Liufu; Huarong Li; Zhuang Mai; Kunhao Hong; Qiaoyan Zhou; Tianhui Jiao; Xidong Mu; Lingyun Yu (Frontiers in Marine Science, 2025)
Myostatin ( Mstn ), a negative regulatory factor in myocytes, has garnered significant attention. This study focused on the Mstn gene and its 24-base-pair mutant in the promoter region of the giant freshwater prawn ( Macrobrachium rosenbergii ), aiming to investigate the regulatory roles of Mstn and its mutant in M. rosenbergii . The research provides theoretical insights into the functional mechanisms of Mstn in crustaceans. Spatiotemporal expression patterns revealed Mstn presence throughout embryonic development and in various body tissues, with peak expression during the gastrula stage and in the hepatopancreas. During the molting cycle, Mstn expression levels decreased in the order of post-molt (A phase), pre-molt (D3 phase), and molting (E phase). Knockdown experiments targeting two genotypes within the Mstn promoter region significantly reduced growth rates and extended molting cycles compared to control group. Further trials on the F2 generation confirmed these findings, highlighting that promoter knockdown influenced the expression of three molting-related genes and slowed the growth rate of M. rosenbergii . This study clarifies the functional role of Mstn in crustacean growth and molting, providing a foundation for understanding its regulatory mechanisms and offering potential applications in aquaculture.

Study on new method of freezing–thawing water replenishment and its mechanical properties for seasonally frozen soil - Miao Wang; Yanxiu Guo; Shangjiu Meng; Anshuang Su; Hailong Mu; Mingwei Hai (Acta Geophysica, 2025)

Mild cognitive impairment is associated with effect of uremic metabolites on gray matter structural changes in end-stage kidney disease - Huijie Yuan; Zhaoyao Luo; Jing Yang; Shaohui Ma; Peng Li; Xinyi Wang; Hang Su; Ronghua He; Junya Mu; Yuchen Zhang (Brain Imaging and Behavior, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Dissolved organic matter mitigates the toxicity of silver nanoparticles to freshwater algae: Effects on oxidative stress and membrane function - Jilai Zhang; Chenglei Hu; Ming Jiang; Qianqian Xiang; Sheng Wang; Youbo Su; Naiming Zhang; Zhihao Si; Yuning Mu; Ran Yang (Environmental Pollution, 2025)

Electronic-ionic dual-conductive framework/channel stabilized Zn anodes for high-performance aqueous Zn-ion batteries - Qian He; Zekai Zhang; Hongchun Mu; Cheng Lian; Quan Li; Haiping Su; Jingkun Li; Honglai Liu (Chemical Engineering Journal, 2025)

Transcriptomics with metabolomics reveals the mechanism of alkaline tolerance in Halomonas alkalicola CICC 11012s - Ruina Liu; Geer Lin; Qi Han; Shuaicheng Mu; Shuang Liu; Su Yao; Lei Zhai (Archives of Microbiology, 2025)

Ecological Responses of Microbially Activated Water Flooding in Ultra-Low-Permeability Reservoirs: A Case Study of the B9 Reservoir in the Triassic Yanchang Formation - Lei Li; Chunhui Zhang; Peidong Su; Hongmei Mu (Journal of Marine Science and Engineering, 2025)
The impact of anthropogenic disturbances during reservoir development on the ecological system—encompassing both environmental and microbial components—has long been overlooked. This study pioneers the investigation into the effects of microbially activated water flooding on both reservoir environments and indigenous microbial communities. We conducted a comprehensive analysis of the B9 Reservoir’s parameters before and after field testing, including the pH, redox potential, conductivity, chemical oxygen demand, biochemical oxygen demand, aqueous-phase cell concentration, aqueous-phase deoxyribonucleic acid (DNA) concentration, oil-phase DNA concentration, and microbial population data. The results demonstrate that environmental parameters exhibit high sensitivity to microbially activated water flooding and effectively explain microbial blooms, while microbial blooms reciprocally alter the environmental conditions, forming a mutually influencing dynamic interplay. The 183-day microbially activated water flooding, while causing detectable impacts on the reservoir environment and microorganisms, did not pose a threat to its ecological stability and contributed to enhanced oil production. In contrast, the 60-month pilot test concluded 27 months earlier exhibited potential destabilization risks to the reservoir ecology. By simultaneously monitoring reservoir environments and microbial dynamics, this research not only addresses potential ecological risks associated with human-driven reservoir development but also provides actionable insights to optimize reservoir management strategies.

Analysis of the Alkaline Resistance Mechanism of Halomonas alkalicola CICC 11012 s by Proteomics and Metabolomics - Ruina Liu; Qi Han; Geer Lin; Shuaicheng Mu; Shuang Liu; Su Yao; Lei Zhai (Current Microbiology, 2025)

Co-culturing Limosilactobacillus fermentum and Pichia fermentans to ferment soybean protein hydrolysates: An effective flavor enhancement strategy - Chenchen Cao; Xueying Song; Yihan Mu; Weizheng Sun; Guowan Su (Innovative Food Science & Emerging Technologies, 2025)

Zinc Transporter 9 (ZnT9) Improves Obesity-Induced Asthenospermia by Attenuating Endoplasmic Reticulum Stress (ERS) - Chen Liang; Mingyang Chen; Zhidan Mu; Xinyan Tian; Wenzhen Zhao; Yarong Hu; Juan Su (Biological Trace Element Research, 2025)

Organic modes of occurrence and evolution mechanism of germanium and lithium in coal: Insights from density functional theory - Ruifeng Mu; Shaoqing Wang; Xiaoling Wang; Haofan Su; Yan Shao (International Journal of Coal Geology, 2025)

Molecular phylogenetic and estimation of evolutionary divergence and biogeography of the family Schizoparmaceae and allied families (Diaporthales, Ascomycota) - Taichang Mu; Yongsheng Lin; Huili Pu; Nemat O. Keyhani; Yuxiao Dang; Huajun Lv; Zhiying Zhao; Zhiang Heng; Ziyi Wu; Chengjie Xiong; Longbing Lin; Yuxi Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Activation of microbial community and enhancement of quality by inoculating Zygosaccharomyces rouxii during the post-fermentation stage of Doubanjiang - Danyu Yan; Qi Qi; Linpei Liu; Lei Feng; Peiyi Deng; Zhuo Chen; Yingchun Mu; Wei Su (Food Research International, 2024)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Quantifying spatiotemporal transfer of soil water and salt between intercrop root zones under alfalfa/spring wheat strip intercropping based on HYDRUS-2D - Kaiqi Su; Le Mu; Tao Zhou; Huimin Yang (Agriculture, Ecosystems & Environment, 2024)

Optimization of latching control for duck wave energy converter based on deep reinforcement learning - Haowen Su; Hao Qin; Zhixuan Wen; Hongjian Liang; Haoyu Jiang; Lin Mu (Ocean Engineering, 2024)

A critical review on the activation of peroxymonosulfate by MOFs for antibiotics degradation: Affecting factor, performance and mechanism - Yiyun Li; Chunhui Zhang; Guifeng Zhao; Zhao Zhang; Peidong Su; Yanxin Li; Yonglin Mu; Weilong Zhou (Journal of Environmental Chemical Engineering, 2024)

A nucleus-targeting fluorescence probe for rapid diagnosis of colorectal cancer - Yonggan Xue; Jimei Chi; Bobin Ning; Lijun Cheng; Wenchen Wang; Qingyu Meng; Liang Huang; Mu Ke; Sen Li; Meng Su; Baoqing Jia (Chemical Engineering Journal, 2024)

Proton transfer induced persistent triplet charge transfer phosphorescence in molecule-doped polymer systems - Shulin Liu; Chensheng Li; Liyun Liao; Yanping Huo; Zhong-Min Su; Fu-Shun Liang; Yingxiao Mu (Chemical Engineering Journal, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Genome-wide analysis of TOPLESS/TOPLESS-RELATED co-repressors and functional characterization of BnaA9.TPL regulating the embryogenesis and leaf morphology in rapeseed - Xiaolong Zhang; Yingying Chen; Hongyu Chen; Chaocheng Guo; Xue Su; Tingting Mu; Bin Feng; Yu Wang; Zhixin Liu; Biaoming Zhang; Yan Li; Haitao Zhang; et al. (Plant Science, 2024)

Essential trace element and phosphatidylcholine remodeling: Implications for body composition and insulin resistance - Wen-Ling Lin; Mu-Ming Chien; Sangopas Patchara; Weu Wang; Amelia Faradina; Shih-Yi Huang; Te-Hsuan Tung; Chien-Sung Tsai; Anatoly V. Skalny; Alexey A. Tinkov; Chun-Chao Chang; Jung-Su Chang (Journal of Trace Elements in Medicine and Biology, 2024)

Constructing efficient lithium salt dissociation solid-state electrolytes with high conductivity and transference number of Li ions for stable all-solid-state lithium batteries - Zengcai Guo; Shimin Liao; Feng Li; Linlin Shi; Bihai Su; Jingbo Mu; Yanming Wang; Zhongkai Huang; Feng Xu; Chaowen Guan (Chemical Engineering Journal, 2024)

Versatile additive for enhancing the stability of Zn Anode: Pyrrolidine-based ionic liquid - Kailimai Su; Hong Zhang; Yan Wang; Xingyun Zhang; Yongbiao Mu; Zhibin Lu; Ye Han; Shanhong Wan; Junwei Lang (Chemical Engineering Journal, 2024)

Analysis of microbial community succession and its metabolic characteristics in the first and second rounds of cave-brewed sauce-flavor Baijiu - Tianxing Zou; Yingchun Mu; Qi Qi; Tingting Ren; Wei Su (Food Bioscience, 2024)

Circ-IP6K2 suppresses tumor progression by modulating the miR-1292-5p/CAMK2N1 signal in clear cell renal cell carcinoma - Jian-ying Tang; Lu Yang; Qing-Jian Wu; Ying Yang; Yuan-Yuan Su; Yi-Rong Chen; Jiao Mu (Functional & Integrative Genomics, 2024)

A critical review on antibiotics removal by persulfate-based oxidation: Activation methods, catalysts, oxidative species, and degradation routes - Yanxin Li; Chunhui Zhang; Guifeng Zhao; Peidong Su; Jianbing Wang; Yiyun Li; Weilong Zhou; Yonglin Mu; Junke Zhang; Wenzong Liu (Process Safety and Environmental Protection, 2024)

Highly stable ultralong organic phosphorescence from a 3D organic supramolecule constructed by halogen bonding and π–π interactions - Aiping Yao; Jing Gao; Yingxiao Mu; Guangfu Li; Kuizhan Shao; Guogang Shan; Yun Geng; Yanping Huo; Zhongmin Su; Xinlong Wang (Chemical Engineering Journal, 2024)

Intercropped alfalfa and spring wheat reduces soil alkali-salinity in the arid area of northwestern China - Kaiqi Su; Le Mu; Tao Zhou; Muhammad Kamran; Huimin Yang (Plant and Soil, 2024)

Upcycling crab shell waste into biochar for treatment of palm oil mill effluent via microwave pyrolysis and activation - Yan Yang; Shin Ying Foong; Yifeng He; Rock Keey Liew; Nyuk Ling Ma; Peter Nai Yuh Yek; Shengbo Ge; Mu. Naushad; Su Shiung Lam (Environmental Research, 2024)

A novel prediction model for integrated district energy system based on secondary decomposition and artificial rabbits optimization - Yan Guo; Qichao Tang; Jo Darkwa; Xuliang Duan; Weiguang Su; Mengjing Jia; Jiong Mu (Energy and Buildings, 2024)

A hybrid approach of anaerobic digestion model no. 1 and machine learning to model and optimize continuous anaerobic digestion processes - Yadong Ge; Junyu Tao; Zhi Wang; Lan Mu; Wei Guo; Zhanjun Cheng; Beibei Yan; Yan Shi; Hong Su; Guanyi Chen (Biomass and Bioenergy, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Isolation and identification of novel umami-enhancing peptides from fermented soybean meal hydrolysate by consecutive chromatography and UPLC–ESI–QTOF–MS/MS - Chenchen Cao; Hui Kang; Yihan Mu; Jianan Zhang; Weizheng Sun; Mouming Zhao; Guowan Su (Food Bioscience, 2024)

Adsorption of humic acid from different organic solid waste compost to phenanthrene, is fluorescence excitation or quenching? - Xinya Su; Ruju Zhang; Huan Cao; Daichen Mu; Liqin Wang; Caihong Song; Zimin Wei; Yue Zhao (Environmental Pollution, 2024)

Multiple isotopes decipher the nitrogen cycle in the cascade reservoirs and downstream in the middle and lower Yellow River: Insight for reservoir drainage period - Jinglong Mu; Shuai Ding; Su Mei Liu; Guodong Song; Xiaoyan Ning; Xiaotong Zhang; Wenqi Xu; Hongmei Zhang (Science of The Total Environment, 2024)

Metagenomics reveals the influence of small microplastics on microbial communities in coastal sediments - Yuhan Zheng; Zhiguo Su; Dantong Liu; Bei Huang; Qinglin Mu; Yunong Li; Donghui Wen (Science of The Total Environment, 2024)

Contrasting characteristics of continental and oceanic deep convective systems at different life stages from CloudSat observations - Jinming Ge; Xiaoyu Hu; Qingyu Mu; Bochun Liu; Zeen Zhu; Jiajing Du; Jing Su; Qinghao Li; Chi Zhang (Atmospheric Research, 2024)

Application of carboxymethyl cellulose sodium (CMCNa) in maize–wheat cropping system (MWCS) in coastal saline-alkali soil - Ge Li; Yuyang Shan; Weibo Nie; Yan Sun; Lijun Su; Weiyi Mu; Zhi Qu; Ting Yang; Quanjiu Wang (Science of The Total Environment, 2024)

Nutrient dynamics in the Yellow River -a case study of different reservoir regulation operations - Jinglong Mu; Hongmei Zhang; Su Mei Liu; Nian Wu; Guodong Song; Shuai Ding; Xiaotong Zhang (Journal of Hydrology, 2024)

Cellular localization and potential ligands of a novel scavenger receptor class B/CD36 protein homolog (Pt-SRB2) identified in the marine crab, Portunus trituberculatus - Su-Ming Zhou; Fang-Mei Lin; Chang-Kao Mu; Chun-Lin Wang; Qi-Cun Zhou; Peng Sun; Fei Yin (Fish & Shellfish Immunology, 2024)

GPX2 acts as an oncogene and cudraflavone C has an anti-tumor effect by suppressing GPX2-dependent Wnt/β-catenin pathway in colorectal cancer cells - Zhuo Wu; Su Zhou; Dan Liang; Lan Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Exploring the heterogeneity of community and function and correspondence of “species-enzymes” among three types of Daqu with different fermentation peak-temperature via high-throughput sequencing and metagenomics - Ying Huang; Dong Li; Yu Mu; Zhiyu Zhu; Yuzhang Wu; Qi Qi; Yingchun Mu; Wei Su (Food Research International, 2024)

Record-breaking marine heatwave in northern Yellow Sea during summer 2018: Characteristics, drivers and ecological impact - Yan Li; Guoyu Ren; Qingyuan Wang; Lin Mu; Qianru Niu; Hanxiang Su (Science of The Total Environment, 2023)

A sustainable strategy to transform cotton waste into renewable cellulose fiber self-reinforcing composite paper - Chan Wang; Jinhui Su; Taoyuan Liu; Shengbo Ge; Rock Keey Liew; Hui Zhang; Mu Naushad; Su Shiung Lam; Hui Suan Ng; Christian Sonne; Wei Fan (Journal of Cleaner Production, 2023)

High-performance inkjet-printed inverted QD-LEDs based on cross-linkable electron regulation layers - Liming Xie; Qing Li; Yuan-Qiu-Qiang Yi; Gengrui Qiu; Omolola Esther Fayemi; Xinju Mu; Zhongsheng Ma; Pengyu Tang; Yang Liu; Wenming Su; Wei Lei; Zheng Cui (Chemical Engineering Journal, 2023)

Lidocaine pretreatment attenuates inflammatory response and protects against sepsis-induced acute lung injury via inhibiting potassium efflux-dependent NLRP3 activation - Kai Su; Xin-Tao Li; Fang-Xiao Hong; Mu Jin; Fu-Shan Xue (Inflammation Research, 2023)

Impact of exposure temperature rise on mass mortality of tidal flat pacific oysters - Jang-Mu Heo; Seong-Su Kim; Do-Youn Kim; Soon Woo Lee; Jung Suk Lee; Min Ho Kang; Seong Eun Kim (Frontiers in Marine Science, 2023)
Oysters are a major commercial and ecological fishery resource. Recently, the oyster industry has experienced mass mortality in summer due to environmental factors. Generally, the survival of oysters in aquatic environments is mainly impacted by environmental stressors such as elevated sea temperatures and reduced salinity; however, the stressors impacting tidal flat oysters that are repeatedly exposed to air remain poorly understood. Hence, we studied the relationship between environmental factors and the survival of tidal flat pacific oysters in Incheon, South Korea, where mass mortality is common. Principal component analysis and Bayesian networks revealed that air temperature (in spring and summer) and sea temperature (in summer) are related to oyster production. In habitats of the tidal flat oysters during the summer, high temperatures of 34.7–35.4°C (maximum 47.6°C) were observed for average durations of 0.8–1.9 hours (maximum 3.6 hours). Furthermore, heat waves occurred for up to 12 consecutive days. Results from the multiple stress test showed that when exposed to 45°C (air temperature) for 4 hours per day, the survival rate of oysters was 42.5% after only 2 days and 0% after 6 days. The findings stemming from the field observations and stress tests suggest that high temperatures during emersion may contribute to mass mortality of oysters in summer, indicating a potential threat to oysters due to climate change. To understand the effects of future thermal stress on oysters more accurately, simultaneous long-term trend analyses and field-based observations are required.

Yield performance, land and water use, economic profit of irrigated spring wheat/alfalfa intercropping in the inland arid area of northwestern China - Le Mu; Kaiqi Su; Tao Zhou; Huimin Yang (Field Crops Research, 2023)

Effects of point and nonpoint source pollution on urban rivers: From the perspective of pollutant composition and toxicity - Yuxuan Liu; Bei Su; Hongxin Mu; Yu Zhang; Ling Chen; Bing Wu (Journal of Hazardous Materials, 2023)

Degradation of levofloxacin from antibiotic wastewater by pulse electrochemical oxidation with BDD electrode - Tao Xu; Xiting Tang; Meiting Qiu; Xiaoliu Lv; Yang Shi; Yihui Zhou; Yanfei Xie; Mu. Naushad; Su Shiung Lam; Hui Suan Ng; Christian Sonne; Shengbo Ge (Journal of Environmental Management, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Efficient denitrification by a salt-tolerant aerobic compound bacteria agent AHM M3: optimizing composition and reduction conditions - H. Ma; Y. Liu; X. Mu; J. Song; X. Su; Y. Wu; R. Han (International Journal of Environmental Science and Technology, 2023)

Transcriptomic analysis of the fat body of resistant and susceptible silkworm strains, Bombyx mori (Lepidoptera), after oral treatment with fenpropathrin - Zi-qin Zhao; Kai-yi Zheng; Yu-tong Zhu; Jun-li Lv; Zhi-hao Su; Xiao-ying Zhang; Wen-qing Lai; Mu-wang Li; Yang-chun Wu; Xue-yang Wang (Pesticide Biochemistry and Physiology, 2023)

Defect modes and localisation of quasi-Lamb waves along a sidewall of corrugated aluminium plates - Qiao-Mu Zhang; Ya-Xian Fan; Le Song; Huan Liu; Yu Su; Zhi-Yong Tao (Wave Motion, 2023)

Effects of slow- and controlled-release nitrogen fertilizers on bacterial and fungal community composition in a double-cropping rice system - Yan Sun; Jian Wang; Wentian Mi; Weiyi Mu; Wanghai Tao; Chao Chen; Wenhai Mi; Lijun Su (Soil and Tillage Research, 2023)

Remediation and recovery of Kariba weed as emerging contaminant in freshwater and shellfish aquaculture system via solvothermal liquefaction - Elfina Azwar; Wan Adibah Wan Mahari; Rock Keey Liew; Muhammad Zulhilmi Ramlee; Meenakshi Verma; William Woei Fong Chong; Wanxi Peng; Hui Suan Ng; Mu. Naushad; Christian Sonne; Su Shiung Lam (Science of The Total Environment, 2023)

Real-time model for wave attenuation using active plate breakwater based on deep reinforcement learning - Hongjian Liang; Hao Qin; Lin Mu; Haowen Su (Ocean Engineering, 2023)

Bamboo-based magnetic activated carbon for efficient removal of sulfadiazine: Application and adsorption mechanism - Fan Yang; Can Jin; Sen Wang; Yujie Wang; Lu Wei; Longhui Zheng; Haiping Gu; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Chemosphere, 2023)

Autochthonous bioaugmentation accelerates phenanthrene degradation in acclimated soil - Haiping Gu; Jie Yan; Yuhao Liu; Xuewei Yu; Yan Feng; Xuanyi Yang; Su Shiung Lam; Mu. Naushad; Cheng Li; Christian Sonne (Environmental Research, 2023)

Research and demonstration on reclaimation of chemical industrial wastewater with high salinity and hardness and purification of reverse osmosis concentrates - Mu Liu; Zehua Li; Mengyuan Duan; Yingqiang Su; Xiaofeng Lin; Huiming Han; Kai Sun (Desalination, 2023)

Perfluorobutanesulfonate exposure induces metabolic disturbances in different regions of mouse gut - Ling Chen; Mengyuan Zhu; Yafeng Liu; Zhongchao Yang; Huan Li; Hongxin Mu; Su Liu; Bing Wu (Science of The Total Environment, 2023)

Quantitative proteomics study on the changes of egg white of yellow preserved primary chicken eggs soaked in alkali solution - Denghui Shi; Wei Su; Yingchun Mu (Food Research International, 2023)

Analysis of the formation mechanism of volatile and non-volatile flavor substances in corn wine fermentation based on high-throughput sequencing and metabolomics - Tianyan Chen; Hanyu Wang; Wei Su; Yingchun Mu; Yexin Tian (Food Research International, 2023)

Effects of Pediococcus acidilactici and Rhizopus Oryzae on microbiota and metabolomic profiling in fermented dry-cure mutton sausages - Li Jiang; Yingchun Mu; Wei Su; Haiyong Tian; Mouming Zhao; Guowan Su; Chi Zhao (Food Chemistry, 2023)

Modification of anaerobic digestion model No.1 with Machine learning models towards applicable and accurate simulation of biomass anaerobic digestion - Yadong Ge; Junyu Tao; Zhi Wang; Chao Chen; Lan Mu; Haihua Ruan; Yakelin Rodríguez Yon; Hong Su; Beibei Yan; Guanyi Chen (Chemical Engineering Journal, 2023)

Effects of Jiuqu inoculating Rhizopus oryzae Q303 and Saccharomyces cerevisiae on chemical components and microbiota during black glutinous rice wine fermentation - Chi Zhao; Wei Su; Yingchun Mu; Lixin Luo; Mouming Zhao; Shuyi Qiu; Guowan Su; Li Jiang (International Journal of Food Microbiology, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

Comparisons of cirrus clouds and their linkages to meteorology at the SACOL and the SGP sites - Zixiang Dong; Jinming Ge; Ang Gao; Zeen Zhu; Jialin Yan; Qingyu Mu; Jing Su; Xuan Yang; Xiaoyu Hu (Atmospheric Research, 2023)

Evaluating the survival of Aspergillus niger in a highly polluted red soil with addition of Phosphogypsum and bioorganic fertilizer - Lingzi Meng; Shang Pan; Limin Zhou; Choochad Santasup; Mu Su; Da Tian; Zhen Li (Environmental Science and Pollution Research, 2022)

Efficient degradation of semi-coking wastewater in three-dimensional electro-Fenton by CuFe2O4 heterocatalyst - Wen-wen Gao; Ting Su; Wei Zhao; Zhi-fang Zhang; Miao Mu; Yong-hui Song; Xue-xue Zhang; Xin-yu Liu (Environmental Science and Pollution Research, 2022)

Multiple low salinity stress modes provided novel insight into the metabolic response of Scylla paramamosain adapting to inland saline-alkaline water - Mingming Niu; Gao Gao; Kangxiang Qin; Yuhao Chen; Huan Wang; Xing Li; Guoling Liang; Chunlin Wang; Changkao Mu; Qiong Su (Frontiers in Marine Science, 2022)
Scylla paramamosain is a high-quality cultivar for saline-alkaline water aquaculture as a euryhaline crustacean species. However, salinity impacts the respiratory metabolism, growth, and survival of marine crustaceans. The metabolic response of crabs adapting to multiple low salinity environments has not been thoroughly studied yet, especially in inland saline-alkaline water. In this study, we analyzed metabolites in the gill and hemolymph of crabs cultured in three different low salinity environments. The results showed that membrane composition (lipids and lipid molecules) and free amino acids played an essential role in the osmoregulation of crabs, and the energy consumption accompanied as well. Meanwhile, S. paramamosain relied on ion transport and energy metabolism under acute/short-term low salinity conditions for osmoregulation. In contrast, amino acids and energy metabolism occupied a leading position in long-term low salinity. Furthermore, taurine and hypotaurine play a vital role in crabs adapting to inland saline-alkaline water. This is the first study to identify the crucial metabolites and key pathways as biomarkers to differentiate the metabolic mechanisms of S. paramamosain under multiple low salinity stress modes based on GC-MS technology, which provided novel insight into the metabolic response of S. paramamosain adapting to inland low salinity saline-alkaline water, and provided theoretical guidance for the aquaculture of S. paramamosain in the inland saline-alkaline water.

Transcriptomic analysis of adaptive mechanisms in response to inland saline-alkaline water in the mud crab, Scylla paramamosain - Guoling Liang; Kangxiang Qin; Yuhao Chen; Mingming Niu; Huan Wang; Chunlin Wang; Changkao Mu; Lizhi Chen; Fangfang Wang; Qiong Su; Ritong Zhu (Frontiers in Marine Science, 2022)
Scylla paramamosain is an important marine aquaculture crustacean on the southeastern coast of China. Given the difficulties of overcrowded coastal aquaculture space and insufficient production, inland saline-alkaline water culture has the potential to alleviate this bottleneck. This study separated 600 crabs into four groups: normal salinity (12-18 ppt, NS), coastal low salinity (3-5 ppt, CS), inland low salinity saline-alkaline (1.5 ppt, IS), and acute low salinity (23 ppt down to 3 ppt, AS), followed by a transcriptomic analysis of the gills. CS-vs-NS, IS-vs-NS, and AS-vs-NS obtained 1154, 1012, and 707 DEGs, respectively. GO analysis showed that the DEGs of the three comparison groups were mainly involved in cellular process, metabolic process, biological regulation, organelle, membrane, extracellular region, binding, and catalytic activity. The findings demonstrate that a significant number of genes are engaged in controlling metabolic processes in the osmoregulation process, and that cell membrane catalysis and different enzymes play a vital part in the environmental adaption process. KEGG enrichment analysis revealed that IS possesses a considerable number of signaling pathways that play important roles in osmoregulation when compared to NS. The cAMP signaling pathway increased the expression of CaM and Na + /K + -ATPase. These findings show that cations like Ca 2+ , Na + , and K + are critical for S. paramamosain to adapt to inland low salinity saline-alkaline water, and that the cAMP signaling pathway regulates their levels. This research provides a theoretical foundation for improving the saline-alkaline aquaculture technology of S. paramamosain .

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Evaluating the stability of Outang landslide in the Three Gorges Reservoir area considering the mechanical behavior with large deformation of the slip zone - Junbiao Yan; Zongxing Zou; Rui Mu; Xinli Hu; Jincheng Zhang; Wen Zhang; Aijun Su; Jinge Wang; Tao Luo (Natural Hazards, 2022)

Attenuation Compensation and Anisotropy Correction in Reverse Time Migration for Attenuating Tilted Transversely Isotropic Media - Xinru Mu; Jianping Huang; Zhenchun Li; Yanli Liu; Laiyuan Su; Junzhou Liu (Surveys in Geophysics, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

The dissolution of fluorapatite by phosphate-solubilizing fungi: a balance between enhanced phosphorous supply and fluorine toxicity - Xiaoqing Shao; Weiduo Hao; Kurt O. Konhauser; Yanan Gao; Lingyi Tang; Mu Su; Zhen Li (Environmental Science and Pollution Research, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Study on Large Deformation Mechanism of Roadway with Close and Multi Coal Seam in Mining - Yongsheng Bao; Dongfang Su; Hongwei Mu (Geotechnical and Geological Engineering, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

New land use regression model to estimate atmospheric temperature and heat island intensity in Taiwan - Chin-Yu Hsu; Uen-Ching Ng; Chiao-Ying Chen; Yu-Cheng Chen; Mu-Jean Chen; Nai-Tzu Chen; Shih-Chun Candice Lung; Huey-Jen Su; Chih-Da Wu (Theoretical and Applied Climatology, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Contrasting the Pb (II) and Cd (II) tolerance of Enterobacter sp. via its cellular stress responses - Zhongquan Jiang; Liu Jiang; Lin Zhang; Mu Su; Da Tian; Tong Wang; Yalin Sun; Ying Nong; Shuijin Hu; Shimei Wang; Zhen Li (Environmental Microbiology, 2020)
Summary Successful application of microorganisms to heavy metal remediation depends on their resistance to toxic metals. This study contrasted the differences of tolerant mechanisms between Pb 2+ and Cd 2+ in Enterobacter sp. Microbial respiration and production of formic acid showed that Enterobacter sp. had a higher tolerant concentration of Pb (>1000 mg l −1 ) than Cd (about 200 mg l −1 ). Additionally, SEM confirmed that most of Pb and Cd nanoparticles (NPs) were adsorbed onto cell membrane. The Cd stress, even at low concentration (50 mg l −1 ), significantly enlarged the sizes of cells. The cellular size raised from 0.4 × 1.0 to 0.9 × 1.6 μm on average, inducing a platelet‐like shape. In contrast, Pb cations did not stimulate such enlargement even up to 1000 mg l −1 . Moreover, Cd NPs were adsorbed homogeneously by almost all the bacterial cells under TEM. However, only a few cells work as ‘hot spots’ on the sorption of Pb NPs. The heterogeneous sorption might result from a ‘self‐sacrifice’ mechanism, i.e., some cells at a special life stage contributed mostly to Pb sorption. This mechanism, together with the lower mobility of Pb cations, caused higher microbial tolerance and removal efficiency towards Pb 2+ . This study sheds evident contrasts of bacterial resistance to the two most common heavy metals.

Cadmium immobilization in aqueous solution by Aspergillus niger and geological fluorapatite - Christopher Uche Okolie; Haoming Chen; Yexin Zhao; Da Tian; Lin Zhang; Mu Su; Zhonquan Jiang; Zhen Li; Huixin Li (Environmental Science and Pollution Research, 2020)

Blood Loss Leads to Increase in Relative Abundance of Opportunistic Pathogens in the Gut Microbiome of Rabbits - Junjie Yang; Jiaming Zhang; Changying Zhao; Zhongtao Gai; Xiaofeng Mu; Ye Wang; Chunling Zhang; Zhenzhen Su; Lihe Gao; Dequan Zhu; Zhiwen Zuo; Xueyuan Heng; et al. (Current Microbiology, 2020)

Integration of transcriptomics, proteomics and metabolomics identifies biomarkers for pulmonary injury by polyhexamethylene guanidine phosphate (PHMG-p), a humidifier disinfectant, in rats - Jung Dae Lee; Hyang Yeon Kim; Keunsoo Kang; Hye Gwang Jeong; Mi-Kyung Song; In Hwan Tae; Su Hyun Lee; Hae Ri Kim; Kyuhong Lee; Sehyun Chae; Daehee Hwang; Suhkmann Kim; et al. (Archives of Toxicology, 2020)

Hydrogen-induced tolerance against osmotic stress in alfalfa seedlings involves ABA signaling - Kiprotich Felix; Jiuchang Su; Rongfei Lu; Gan Zhao; Weiti Cui; Ren Wang; Hualun Mu; Jin Cui; Wenbiao Shen (Plant and Soil, 2019)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Inhibition of SIRT1/2 upregulates HSPA5 acetylation and induces pro-survival autophagy via ATF4-DDIT4-mTORC1 axis in human lung cancer cells - Ning Mu; Yuanjiu Lei; Yu Wang; Yingying Wang; Qinghui Duan; Guilin Ma; Xiangguo Liu; Ling Su (Apoptosis, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Reduction of Pb availability during surficial leaching in different types of soils with addition of apatite and oxalic acid - Chenmeng Guo; Weitao Tian; Zhijun Wang; Feiyu Han; Mu Su; Yiling Wu; Zhen Li; Shuijin Hu (Journal of Soils and Sediments, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

A new insight into lead (II) tolerance of environmental fungi based on a study of Aspergillus niger and Penicillium oxalicum - Da Tian; Zhongquan Jiang; Liu Jiang; Mu Su; Zheye Feng; Lin Zhang; Shimei Wang; Zhen Li; Shuijin Hu (Environmental Microbiology, 2019)
Summary Environmental microorganisms have been widely applied in heavy metal remediation. This study explored the mechanisms of lead tolerance of two typical filamentous fungi, Aspergillus niger and Penicillium oxalicum . It is shown that the mechanisms of reducing Pb toxicity by these two fungi have three major pathways. The secreted oxalic acid can react with Pb (II) to form insoluble Pb minerals, primarily lead oxalate. Then, the enhanced biosorption via forming new border of cell wall prevents the transportation of Pb (II) into hypha. In addition, the fungal activity could be maintained even at high Pb concentration due to the intracellular accumulation. It was confirmed that A. niger has the higher Pb tolerance (up to 1500 mg l −1 Pb level) compared with P. oxalicum (up to 1000 mg l −1 ). Meanwhile, Pb levels below 1000 mg l −1 partially stimulate the bioactivity of A. niger , which was confirmed by its elevated respiration (from 53 to 63 mg C l −1 medium h −1 ). This subsequently enhanced microbial functions of A. niger to resist Pb toxicity. A better understanding of Pb tolerance of these two fungi sheds a bright future of applying them to remediate lead‐contaminated environments.

Focusing one-stationary bistatic forward-looking synthetic aperture radar based on squint minimization and modified nonlinear chirp scaling algorithm - Mu Liang; Weimin Su; Chao Ma; Hong Gu; Jianchao Yang (International Journal of Remote Sensing, 2018)

Remediation of lead-contaminated water by geological fluorapatite and fungus Penicillium oxalicum - Da Tian; Wenchao Wang; Mu Su; Junyi Zheng; Yuanyi Wu; Shimei Wang; Zhen Li; Shuijin Hu (Environmental Science and Pollution Research, 2018)

Effect of cultivar and growing medium on the fruit quality attributes and antioxidant properties of tomato (Solanum lycopersicum L.) - Shimeles Tilahun; Mu Hong Seo; Do Su Park; Cheon Soon Jeong (Horticulture, Environment, and Biotechnology, 2018)

Foliar nutrient resorption responses of three life-form plants to water and nitrogen additions in a temperate desert - Gang Huang; Yan-gui Su; Xiao-han Mu; Yan Li (Plant and Soil, 2018)

A high throughput method for rapid screening of chitosanase-producing fungal strain under acidic conditions - Su Ding; Gui-Guang Chen; Zhi-Qun Liang; Wei Zeng; Mu-Ming Cao; Guo-Pin Chen; Shu-Yu Xie; Wei Li (World Journal of Microbiology and Biotechnology, 2016)

Baseline sensitivity and control efficacy of antibiosis fungicide tetramycin against Botrytis cinerea - Yingying Song; Leiming He; Lele Chen; Yupeng Ren; Hongbao Lu; Su Geng; Wei Mu; Feng Liu (European Journal of Plant Pathology, 2016)

Age, introduction of solid feed and weaning are more important determinants of gut bacterial succession in piglets than breed and nursing mother as revealed by a reciprocal cross‐fostering model - Gaorui Bian; Shouqing Ma; Zhigang Zhu; Yong Su; Erwin G. Zoetendal; Roderick Mackie; Junhua Liu; Chunlong Mu; Ruihua Huang; Hauke Smidt; Weiyun Zhu (Environmental Microbiology, 2016)
Summary A reciprocal cross‐fostering model with an obese typical Chinese piglet breed and a lean Western breed was used to identify genetic and maternal effects on the acquisition and development gut bacteria from birth until after weaning. Pyrosequencing of 16S rRNA genes results revealed an age‐ and diet‐dependent bacterial succession process in piglets. During the first 3 days after birth, the bacterial community was relatively simple and dominated by Firmicutes with 79% and 65% relative abundance for Meishan and Yorkshire piglets, respectively. During the suckling period until day 14, the piglet breed and the nursing mother lead to increasing differentiation of the fecal bacterial community, with specific bacteria taxa associated with breed, and others with the nursing sow most likely due to its milk composition. Although the effect of nursing mother and the breed were evident through the suckling period, the introduction of solid feed and subsequent weaning were the major events occurring that dominated succession of the gut microbiota in the early life of piglets. This piglet cross‐fostering model is a useful tool for studying the effects of diet, host genetics and the environment on the development and acquisition of the gut microbiota and over longer studies the subsequent impact on growth, health and performance of pigs.

Erratum to: Methylation of the miR-126 gene associated with glioma progression - Hongwei Cui; Yongping Mu; Lei Yu; Yaguang Xi; Rune Matthiesen; Xiulan Su; Wenjie Sun (Familial Cancer, 2016)

Methylation of the miR-126 gene associated with glioma progression - Hongwei Cui; Yongping Mu; Lei Yu; Ya-guang Xi; Rune Matthiesen; Xiulan Su; Wenjie Sun (Familial Cancer, 2016)

Derivation of marine water quality criteria for metals based on a novel QICAR-SSD model - Cheng Chen; Yunsong Mu; Fengchang Wu; Ruiqing Zhang; Hailei Su; John P. Giesy (Environmental Science and Pollution Research, 2015)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

SNAP25 Ameliorates Sensory Deficit in Rats with Spinal Cord Transection - Wei Wang; Fang Wang; Jia Liu; Wei Zhao; Qi Zhao; Mu He; Bao-Jiang Qian; Yang Xu; Ran Liu; Su-Juan Liu; Wei Liu; Jin Liu; et al. (Molecular Neurobiology, 2014)

Prognostic significance of TBX2 expression in non-small cell lung cancer - Bo Hu; Hai-Ping Mu; Yu-Qing Zhang; Chong-Yi Su; Jian-Tao Song; Chong Meng; Dong-Xing Liu (Journal of Molecular Histology, 2014)

The Novel Heterocyclic Trioxirane [(1,3,5-Tris Oxiran-2-yl)Methyl)-1,3,5-Triazinane-2,4,6-Trione (TATT)] Exhibits a Better Anticancer Effect than Platinum-Based Chemotherapy by Induction of Apoptosis and Curcumin Further Enhances its Chemosensitivity - Chun-Li Su; Ying-Ti Wang; Mu-Hsin Chang; Kang Fang; Kwunmin Chen (Cell Biochemistry and Biophysics, 2014)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)

Whole exome sequencing identifies mutation of EDNRA involved in ACTH-independent macronodular adrenal hyperplasia - Jie Zhu; Liang Cui; Wei Wang; Xing-Yi Hang; A-Xiang Xu; Su-Xia Yang; Jing-Tao Dou; Yi-Ming Mu; Xu Zhang; Jiang-Ping Gao (Familial Cancer, 2013)

Relations between stimulation of mesolimbic dopamine and place conditioning in rats produced by cocaine or drugs that are tolerant to dopamine transporter conformational change - Gianluigi Tanda; Su Min Li; Maddalena Mereu; Alexandra M. Thomas; Aaron L. Ebbs; Lauren E. Chun; Valeria Tronci; Jennifer L. Green; Mu-Fa Zou; Theresa A. Kopajtic; Amy Hauck Newman; Jonathan L. Katz (Psychopharmacology, 2013)

Identification of the promoter region and genetic mutations of the porcine GALP gene - Lina Su; Shuqi Mei; Hu Tao; Xianwen Peng; Xiaojie Sun; Huayu Wu; Xuying Zhang; Mu Qiao; Fenge Li (Molecular Biology Reports, 2013)

Indoor air pollution and risk of lung cancer among Chinese female non-smokers - Lina Mu; Li Liu; Rungui Niu; Baoxing Zhao; Jianping Shi; Yanli Li; Mya Swanson; William Scheider; Jia Su; Shen-Chih Chang; Shunzhang Yu; Zuo-Feng Zhang (Cancer Causes & Control, 2013)

Environmental capacity of petroleum hydrocarbon pollutants in Jiaozhou Bay, China: Modeling and calculation - Keqiang Li; Ying Su; Jun Ying; Xiulin Wang; Jinbo Mu (Journal of Ocean University of China, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Cathepsin B SNPs elevate the pathological development of oral cancer and raise the susceptibility to carcinogen-mediated oral cancer - Mu-Kuan Chen; Shih-Chi Su; Chiao-Wen Lin; Chiung-Man Tsai; Shun-Fa Yang; Chia-Jui Weng (Human Genetics, 2012)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

Effects of pH, MES, arabinogalactan-proteins on microspore cultures in white cabbage - Su-xia Yuan; Yan-bin Su; Yu-mei Liu; Zhi-yuan Fang; Li-mei Yang; Mu Zhuang; Yang-yong Zhang; Pei-tian Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

OsPFA-DSP1, a rice protein tyrosine phosphatase, negatively regulates drought stress responses in transgenic tobacco and rice plants - Bing Liu; Jieqiong Fan; Yang Zhang; Peiqiang Mu; Peng Wang; Jianbin Su; Huihuang Lai; Shaowu Li; Dongru Feng; Jinfa Wang; Hongbin Wang (Plant Cell Reports, 2012)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Primary scientific results of Chang’E-1 lunar mission - ZiYuan Ouyang; ChunLai Li; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; JianJun Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; BaoChang Zhao; et al. (Science China Earth Sciences, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Triaxial ellipsoid models of the Moon based on the laser altimetry data of Chang’E-1 - WenRui Wang; Fei Li; JianJun Liu; Xin Ren; XiaoDuan Zou; LingLi Mu; JianGuo Yan; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Evaluation of Combined Toxicity of Phenols and Lead to Photobacterium phosphoreum and Quantitative Structure–Activity Relationships - L. M. Su; Y. H. Zhao; X. Yuan; C. F. Mu; N. Wang; J. C. Yan (Bulletin of Environmental Contamination and Toxicology, 2010)

Molecular basis of the internalization of bovine immunodeficiency virus Tat protein - Gang Deng; Yang Su; Junjie Mu; Rina Sha; Yunqi Geng; Wentao Qiao; Qimin Chen (Virus Genes, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

PaCDPK1, a gene encoding calcium-dependent protein kinase from orchid, Phalaenopsis amabilis, is induced by cold, wounding, and pathogen challenge - Tsung-Mu Tsai; Ying-Ru Chen; Tien-Wen Kao; Wen-Su Tsay; Chiou-Ping Wu; Ding-Ding Huang; Wen-Huei Chen; Ching-Chun Chang; Hao-Jen Huang (Plant Cell Reports, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)